Analysis on the current situation and influencing factors of psychological contract violation of ICU nurses (ICU护士心理契约违背现状及影响因素分析) - LIU Si (刘思); DU Hui (杜慧); ZOU Xiumei (邹秀梅); SUN Zhongwen (孙仲文); HUANG Zhongying (黄中英) (Association of Integrative Nursing, 2023)
Objective To investigate the status quo and influencing factors of psychological contract violation among ICU nurses in Guangzhou. Methods A total of 176 ICU nurses from 7 Grade III, Class A hospitals in Guangzhou were selected by convenience sampling, and an online survey was conducted by using self-made general information questionnaire and Psychological Contract Violation Scale. Results A total of 176 e-questionnaires were completed and 167 valid e-questionnaires were recovered. The score of Psychological Contract Violation Scale for nurses was (69. 13±11. 75), and the item average score was (3. 29±0. 56). The results of multiple Regression analysis showed that the highest education level, the relationship between doctors and nurses, and whether or not they had participated in the career planning lectures or activities organized by the unit were the influential factors of psychological contract violation (P＜0. 01) . Conclusion The psychological contract violation of ICU nurses is at middle level. Nursing managers should carry out targeted intervention measures to regulate nurses and train their ability to control their emotions, enhance the level of job embeddedness, enhance their sense of responsibility and loyalty to the unit, create a good organizational climate and reduce their psychological contract violations. (目的 调查广州市ICU护士心理契约违背现状及影响因素。方法 采用便利抽样法, 选择2022年4月-6月广东省广州市7家三级甲等医院的176名ICU护士为研究对象, 采用一般调查问卷、心理契约违背量表, 通过"问卷网"平台进行调查。结果 填写电子问卷176份, 回收有效电子问卷167份。护士心理契约违背量表得分为(69. 13±11. 75)分, 条目均分(3. 29±0. 56)分。多重线性回归分析结果显示, 最高学历、科室医护合作关系、是否参加过单位组织的职业规划讲座或活动, 是护士心理契约违背的影响因素(P＜0. 01) 。结论 ICU护士心理契约违背处于中等水平。护理管理者应实施有针对性的干预措施, 调节护士情绪控制能力, 培养其驾驭情绪的能力, 增强工作嵌入水平, 增强其对单位的责任感和忠诚度, 营造良好的组织氛围, 降低其心理契约违背。)